Experimental testing and analysis of the axial behaviour of intermeshed steel connections. Issue 2 (3rd February 2022) - McGetrick, Patrick J.; Matis, Pantelis; Martin, Tony; Robinson, Desmond; Laefer, Debra F.; Al-Sabah, Salam; Truong-Hong, Linh; Huynh, Minh Phuoc; Schultz, Arturo E.; Le, Jia-Liang; Shemshadian, Mohammad E.; Labbane, Ramzi
Abstract : This paper presents the work carried out on a collaborative tripartite project between the USA, Republic of Ireland and Northern Ireland to create and investigate the design, development and testing of a new class of intermeshed steel connections (ISCs) that do not rely on field welding and minimise bolting, thus targeting the facilitation of fast disassembly of steel structures and material reuse. This research took advantage of fully automated, precise, advanced manufacturing cutting technologies (e.g. laser, waterjet and high-definition plasma cutting) to achieve a connection method in steel that previously was only possible in materials such as timber, with the potential to revolutionise the steel construction industry. The paper outlines the ongoing research work by the collaborative team, focusing on the design, fabrication, finite-element analysis (FEA) and scaled experimental testing of side ISCs for the flanges of open sections, which included the use of state-of-the-art digital image correlation technology for non-contact measurements. A simplified connection design procedure is presented based on yielding of the side plates. This design procedure is refined based on the results of experimental testing and FEA of the local axial behaviour of the flange connection, addressing stress concentrations in the flange, fabrication tolerances and material overstrength.